Progresses in microRNA Delivery Using Synthetic Nanovectors in Cancer Therapy - Javanmardi, Sanaz; Aghamaali, Mahmoud R.; Abolmaali, Samira Sadat; Tamaddon, Ali Mohammad (Current Pharmaceutical Design, 2018)
MicroRNAs are small noncoding RNAs with key roles in gene expression. It has been revealed that aberrant expression of microRNAs is related to gene expression abnormality, and they have the potential to be used as anti-cancer drugs. However, the delivery of microRNAs is limited due to barriers, such as low uptake and insufficient endosomal release, intracellular nucleases degradation, phagocytic elimination, and renal filtration. To overcome these issues, novel delivery systems are developed for improving the efficiency of microRNAs therapy ranging from viral to synthetic; some are further developed with targeted ligands for active targeting purposes. Such delivery systems provide efficient cellular uptake and endosomal release as well as low cytotoxicity and minimum unwanted host immune response. Nevertheless, more complementary studies are warranted before being applied in human studies. This review deals with recent updates on the challenges and achievements of the various nanotechnology-based gene delivery vehicles with a special emphasis on the miRNA delivery in cancer therapy. In addition, we attempted to categorize the designed delivery systems based on miRNA therapeutic molecule. The related cellular signaling pathways and pharmacological action against cancer promotion have also been highlighted.
Keywords: delivery system